The mechanical properties and conduction of solid polyurethane electrolytes depending on the methods of synthesis and LiClO4 content as addition - Leszkowski, K.; Strankowski, M.; Miszczyk, A.; Haponiuk, J. T. (Polimery, 2011)
Two methods for the synthesis of polyurethane elastomers as polymeric matrix for the studied systems using as raw materials 4,4'-diphenylmethane diisocyanate (MDI), oligo(oksytetramethylene)diol (PTMG) and 1,4-butanediol (BDO) have been presented. In the first method (variant A), lithium perchlorate (LiClO4) was added in situ during the elongation of the prepolymer chain with BDO, while in the second (variant B) the lithium salt was added to the plasticized polyurethane in a twin-screw laboratory extruder. The obtained solid polyurethane electrolytes were characterized with FTIR-ATR spectroscopy (Fig. 1), their static and dynamic mechanical properties evaluated and density determined (Table 1, Figs. 2—8). The alternating current (AC) impendance spectroscopy method was used to determine the ionic conductivity of the products (Figs. 9—14). Conductivity values were found to depend on the adopted synthesis variant and the amount of doped LiClO4. The highest value of 1.04ź10-7 S/cm was observed for the product synthesized according to variant B containing 3 wt. % of the doped lithium salt.